Photophysical properties and energy transfer mechanism in PFO/TiO2 /MEH-PPV nanocomposite thin films - Sameer Albati,; Mohammad Hafizuddin Hj. Jumali,; Al-Asbahi, Bandar Ali; Qaid, Saif M.H.; Yap, Chi Chin (Penerbit Universiti Kebangsaan Malaysia, 2020)
Improvement in photophysical properties of poly-9,9-dioctylfluorene (PFO)/10 wt. % TiO2 nanoparticle thin film as a result of systematic additions of poly(2-methoxy-5(2-ethylhexyl)-1,4-phenylenevinylene (MEH-PPV) were investigated. The nanocomposite blends were prepared with additions of MEH-PPV up to 3.0 wt. % of the total weight. All blends were prepared using the solution blending method and subsequently spin-coated onto glass substrates. The UV-Vis absorption and photoluminescence characterizations showed the intensification of the primary-color emissions of the thin films with the Förster resonance as the primary energy transfer mechanism from PFO to MEH-PPV. Important photophysical parameters, such as the Förster radius (Ro ) excited state lifetime (τ), fluorescence quantum yield of the donor (φ), quenching constant (ksv), quenching rate constant (kq ), distance between the donor and acceptor (R), energy transfer lifetime (τET), and energy transfer rate (kET) display better values with increasing the contents of MEH-PPV by 2.5 wt. %, suggesting an ordered improvement on the photophysical properties of the thin film. Finally, a possible underlying mechanism describing the enhancement of the photophysical properties was proposed.